The distribution of nonprincipal eigenvalues of singular second-order linear ordinary differential equations - Juan Pablo Pinasco (International Journal of Mathematics and Mathematical Sciences)
We obtain the asymptotic distribution of the nonprincipal eigenvalues associated with the singular problem x″+λq(t)x=0 on an infinite interval [a,+∞). Similar to the regular eigenvalue problem on compact intervals, we can prove a Weyl-type expansion of the eigenvalue counting function, and we derive the asymptotic behavior of the eigenvalues.